2023
DOI: 10.1073/pnas.2302313120
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and predictors of wind energy opposition in North America

Leah C. Stokes,
Emma Franzblau,
Jessica R. Lovering
et al.

Abstract: Addressing climate change requires societies to transition away from fossil fuels toward low-carbon energy, including renewables. Unfortunately, large wind projects have proven politically controversial, with groups opposing them across advanced economies. To date, there are few large-scale, systematic studies to identify the prevalence and predictors of opposition to wind energy projects. Here, we analyzed a dataset of wind energy projects across the United States and Canada between 2000 and 2016. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It may also expand the energetic capacity of coastal nations whose potential for onshore energy infrastructure is limited. Recent studies in North America have also linked opposition to wind farm development with variable socio-economic and ethnic privileges [40], revealing that concern over development is a demographically variable phenomenon. Offshore wind farms, by contrast, offer greater opportunity for energy generation [41] from development areas that are largely out of sight and mind to many onshore communities [42], although the impact of offshore developments on natural marine resources as well as coastal heritage landscapes (as at St Abb's Head in Scotland, [43]) have also generated opposition to development.…”
mentioning
confidence: 99%
“…It may also expand the energetic capacity of coastal nations whose potential for onshore energy infrastructure is limited. Recent studies in North America have also linked opposition to wind farm development with variable socio-economic and ethnic privileges [40], revealing that concern over development is a demographically variable phenomenon. Offshore wind farms, by contrast, offer greater opportunity for energy generation [41] from development areas that are largely out of sight and mind to many onshore communities [42], although the impact of offshore developments on natural marine resources as well as coastal heritage landscapes (as at St Abb's Head in Scotland, [43]) have also generated opposition to development.…”
mentioning
confidence: 99%
“…While claims of broad-based distrust do not appear to be well supported, it is important to note that distrust and skepticism, by even a small number of people, can be highly detrimental if they are people in positions of power (e.g., Presidents/PMs, senior government officials, CEOs, or a small but crucial voting block) that decrease support for climate policy [32], or if they actively stall mitigation efforts [6,[33][34][35]. Moreover, researchers have found that traditional survey methods (i.e., direct survey questions) may underestimate the proportion of climate change skeptics, especially among the top 20% of the income distribution in the United States and conservatives in Germany [36].…”
Section: The Current State Of Trust In Climate Science and Climate Sc...mentioning
confidence: 99%
“…While claims of broad-based distrust do not appear to be well supported, it is important to note that distrust and skepticism, by even a small number of people, can be highly detrimental if they are people in positions of power (e.g., Presidents/PMs, senior government officials, CEOs, or a small but crucial voting block) that decrease support for climate policy (Engels et al, 2013), or if they actively stall mitigation efforts (Franta, 2022;Oreskes & Conway, 2010;Stokes et al, 2023;Winter et al, 2022). Moreover, researchers have found that traditional survey methods (i.e., direct survey questions) may underestimate the proportion of climate change skeptics, especially among the top 20% of the income distribution in the United States and conservatives in Germany (Beiser-McGrath & Bernauer, 2021).…”
Section: The Current State Of Trust In Climate Science and Climate Sc...mentioning
confidence: 99%